Traditional individual and environmental determinants of healthy eating in Vihiga County, Western Kenya - Penafiel, Daniela; Termote, Céline; Damme, Patrick van (MDPI, 2022)
Traditional ethnic groups in Kenya are unlikely to eat a healthy and diversified diet due to many individual and environmental factors, which may result in poor health status. Therefore, the determinants of eating behavior need to be identified prior to any public health action. For this study, focus group discussions (15 in total) in a double-layer design were conducted, comprising adult men and women from 5 villages of Vihiga County. Questions explored knowledge; barriers and cues to action toward eating a healthy diet containing a variety of foods; including indigenous food species. We found that healthy eating concepts are known; however, several taboos that restrict food consumption reduce local diet quality in terms of diversity. Nutrition education is a cue to action. We identified several individual and environmental determinants of eating behavior in the studied communities. Public health action should focus on supporting healthy eating behaviors and refining some taboos’ beliefs.